Analysis of Individual and Occupational Factors with Complaints of Musculoskeletal Disorders in Swallow Nest Cleaning - Irlangga Wisnu Wardana; Ahmad Rido'i Yuda Prayogi; Dani Nasirul Haqi; Endang Dwiyanti (The Indonesian Journal of Occupational Safety and Health, 2023)
Introduction: Workers of swallow nest industry are at risk of experiencing musculoskeletal disorders due to monotonous swallow nest cleaning activity which puts heavy load on their extremity area of the upper body. This research seeks to analyze the relationships of age, gender, nutritional status, exercise habits, working hours, and working position with complaints of musculoskeletal disorders in swallow nest cleaning workers at PT. Lentera Alam Nusantara. Method: This type of research uses observational with a cross-sectional approach. The population in this study were all workers in the cleaning and washing section of swallow nests at PT. Lentera Alam Nusantara Surabaya, totaling 50 people. Determination of the number of samples using simple random sampling lemmeshow formula, obtained a sample of 36 workers. Results: The majority of workers are 35 years old, female, obese nutritional status, rarely exercise, have 8 hours of work, moderate work position, and the majority have moderate muculoskeletal complaints. Based on the analysis test results using the spearman test, it shows that the factors that have a significant p-value <0.05 include ages, gender, nutrition status, exercise habits, and working hours. Conclusion: Thus, it can be concluded that there is a relationship between age, gender, nutrition status, exercise habits, and working hours with complaints of musculoskeletal disorders.